CHANGE OF NUTRIENT AND BIOACTIVE COMPONENTS IN BOVINE COLOSTRUM AFTER SPRAY DRYING - Thi Hoa Vien, Do; Quang Hoa, Le (Vietnam Journal of Science and Technology, 2017)
Bovine colostrum powder (BCP) was obtained by using spray drying method with the inlet temperature  at  120oC  and  the  outlet  temperature  at  60oC. Nutrient  and  bioactive  components such as protein,  lipid,  lactose, mineral, glycoprotein (e.g.  lactoferrin) and  the  immunoglobulins IgG, IgA and IgM in BCP  were analyzed before and after spray drying  process.  Experimental  results  showed  that  the  average  values  for  total  protein,  lipid,  lactose, mineral, lactoferrin in BCP were 25.31 %, 26.63 %, 33.92 %, 7.23 %, 1.497 %; and the average values for IgG, IgA and IgM in BCP were 136.31 mg/g, 27.31 mg/g and 4.22 mg/g respectively. The  obtained  results  also  illustrated  that  these  compositions  in BCP  samples were  decreased from 0.87 to 62.67 % compared with those in pasteurized colostrums samples, depending on the nature of each component in the colostrums. For instance, lactoferrin and total protein were lost 43.3 % and 34.76 %; IgG, IgA and IgM were decreased 22.57 %, 15.48 % and 45.41 %; while lactose and minerals were just lost 3.66 % and 0.87 %.